Lessons learnt from design and construction of dams in Brazil - Cruz, Paulo Teixeira da (Journal of Nepal Geological Society, 2000)
This paper deals with design and construction of dams built in Brazil. A brief introduction on the history of these dams is followed by the main types of dams, that due to the environment, site topography, climate, foundation conditions and borrow materials, have been considered the most adequate and economical both for irrigation purposes or power generation. A second item deals with peculiar behaviour of the residual soils used as construction materials regarding flow aspects and construction pore pressures. The use of saprolitic soils is also discussed as well as of rock materials that disintegrate under drying and wetting cycles. The shear strength parameters of these materials obtained in laboratory and field tests are presented. The compressibility and the stability of the dams, and the measured flows through the foundations are reported.